From the intellectual superiority to the moral superiority in Aeschylus’ Oresteia - Bertolín Cebrián, Reyes (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2018)
The topic of this article is the concept of Justice in Aeschylus’ Oresteia. Justice is understood as moral superiority and it is associated with intellectual and rational superiority. In the classical world positive intellectual characteristics were almost exclusively attributed to men. This is a change from Homeric times, when women were valued also for their intelligence. Since the heroines in classical tragedy belong to the Homeric world and do not conform to the classical standards of femininity, there is a disjuncture in the perception of women that places them at a disadvantage. Through the analysis of passages where verbs of thinking and learning are used one can observe the transition from the Homeric woman to the classical one which is parallel to the transition of the struggle to establish intellectual superiority to the imposition of revealed knowledge.
Keywords: justice and women; verbs of thinking; verbs of learning; male rationality.